Reinventing Liberty - Price, Fiona L. (Book collections on Project MUSE., 2016)
Redefines the British historical novel as a key site in the construction of British national identity. The British historical novel has often been defined in the terms set by Walter Scott's fiction, as a reflection on a clear break between past and present. Returning to the range of historical fiction written before Scott, Reinventing Liberty challenges this view by returning us to the rich range of historical novels written in the late eighteenth-century. It explores how these works participated in a contentious debate concerning political change and British national identity. Ranging across well-known writers, like William Godwin, Horace Walpole and Frances Burney, to lesser-known figures, such as Cornelia Ellis Knight and Jane Porter, Reinventing Liberty reveals how history becomes a site to rethink Britain as 'land of liberty' and it positions Scott in relation to this tradition. Key Features. Recovers the richness of the historical novel and history writing before Walter Scott, including the contribution of women writers to this debate Explores how historical fiction probes anxieties at the rise of commerce, the question of empire, and radical political change Rewrites our understanding of Scott and his relation to the earlier British historical novel